Perkembangan Masa Puber - Deyaninda Safira; Linda Yarni (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Puberty development is a critical phase in an individual's life marked by significant physical, emotional, social and cognitive changes. This phase occurs when the body experiences rapid growth and hormonal changes that affect various aspects of a teenager's life. Physical development includes growth of reproductive organs, secondary development, and increases in physical capacity. Apart from that, teenagers also experience emotional developments such as emotional turmoil and the search for self-identity. Adolescent social development involves identity exploration, interaction with peers, and adjustment to social norms. Cognitive development also develops with increasingly mature abstract and analytical thinking abilities. This study illustrates the importance of an in-depth understanding of pubertal development to support the well-being and optimal growth of adolescents.